Resolution of MALDI-TOF compared to whole genome sequencing for identification of Bacillus species isolated from cleanrooms at NASA Johnson Space Center - Mazhari, Farnaz; Regberg, Aaron B.; Castro, Christian L.; LaMontagne, Michael G. (Frontiers in Microbiology, 2025)
IntroductionBacteria are frequently isolated from surfaces in cleanrooms, where astromaterials are curated, at NASA’s Lyndon B. Johnson Space Center (JSC). Bacillus species are of particular interest because endospores can endure extreme conditions. Current monitoring programs at JSC rely on culturing microbes from swabs of surfaces followed by identification by 16S rRNA sequencing and the VITEK 2 Compact bacterial identification system. These methods have limited power to resolve Bacillus species. Whole genome sequencing (WGS) is the current standard for bacterial identification but is expensive and time-consuming. Matrix-assisted laser desorption - time of flight mass spectrometry (MALDI-TOF MS), provides a rapid, low-cost, method of identifying bacterial isolates and has a higher resolution than 16S rRNA sequencing, particularly for Bacillus species; however, few studies have compared this method to WGS for identification of Bacillus species isolated from cleanrooms.MethodsTo address this, we selected 15 isolates for analysis with WGS and MALDI-TOF MS. Hybrid next-generation (Illumina) and 3rd-generation (nanopore) sequencing were used to draft genomes. Mass spectra, generated with MALDI-TOF MS, were processed with custom scripts to identify clusters of closely related isolates.ResultsMALDI-TOF MS and WGS identified 13/15 and 9/14 at the species level, respectively, and clusters of species generated from MALDI-TOF MS showed good agreement, in terms of congruence of partitioning, with phylotypes generated with WGS. Pairs of strains that were > 94% similar to each other, in terms of average amino acid identity (AAI) predicted by WGS, consistently showed cosine similarities of mass spectra >0.8. The only discordance was for a pair of isolates that were classified as Paenibacillus species. This pair showed relatively high similarity (0.85) in terms of MALDI-TOF MS but only 85% similarity in terms of AAI. In addition, some strains isolated from cleanrooms at the JSC appeared closely related to strains isolated from spacecraft assembly cleanrooms.DiscussionSince MALDI-TOF MS costs less than whole genome sequencing and offers a throughput of hundreds of isolates per hour, this approach appears to offer a cost-efficient option for identifying Bacillus species, and related microbes, isolated during routine monitoring of cleanrooms and similar built environments.